Investigations on growth and characterisation of 2-hydroxyanilinium 3, 5-dinitrobenzoate single crystal. (April 2015) - Rathika, A.; Ganapathi Raman, R.
Abstract : A non-centrosymmetric organic single crystal 2-hydroxyanilinium 3, 5-dinitrobenzoate (2HADB) has been grown by slow evaporation solution technique at room temperature using ethanol as solvent. The unit cell parameters and the crystallinity nature of the grown crystal were determined by single crystal and powder X-ray diffraction studies. Fourier transform infrared (FTIR) spectral analysis confirms the various functional groups present in the crystal. The thermal stability and melting point of the material have been investigated by thermogravimetric analysis/differential thermal analysis (TGA/DTA) analysis. The optical absorption studies of the grown crystal were identified by ultraviolet-visible (UV-Vis) spectral analysis. Second harmonic generation (SHG) efficiency of the grown crystal was tested by Kurtz and Perry powder method using Nd:YAG laser as a source.